(untitled) (Bangladesh Journal of Zoology, 2020)
Tilapia (Oreochromis niloticus) has been gaining ground in cultivation and sale in Bangladesh but due to price hike of fish feed the culture of this fish faced many challenges. In the present study, the optimal level of dietary moringa (Moringa oleifera) leaf powder was used as feed supplement to determine the growth performances, some selective blood parameters and bacterial load in Nile tilapia, Oreochromis niloticus. Commercial feed with processed moringa leaf at 0g/kg, 100g/kg and 200g/kg diet was used. The diet containing 100g moringa leaf/kg diet resulted in increased weight gain, average daily gain, specific growth rate, condition factor and survival rate. A significant (p<0.05) reduction in RBC and WBC were observed as increasing amount of processed moringa leaf was added in the diets but no significant differences were observed among the three different rearing conditions. In most of the cases, the diet containing 100g moringa leaf powder/kg diet displayed lower amount of bacterial count but no significant improvement was found in bacterial load among the different treatment conditions. The results suggest that addition of moringa leave powder with commercial diet at 100g/kg diet may be better for growth, survival, immune response and microbial challenge of Nile tilapia. Bangladesh J. Zool. 48(1): 151-166, 2020